(untitled) (Journal of Oriental Studies, 2016)
this article discusses theeraof globalizationin india and itsimpacton economic growth.each newevent in theworld economy and politicsonce again confirms theglobalinterdependence of nations. an important taskis to determine theactionand intensity ofthat connection. Globalization,about which so muchis said and writtenin our time, has brought most of the developingcountriesnew opportunities, problems and challengesthat hinderthe weakercounterpartiesand pushforward moreadaptive.